Characteristics of Children’s Literature in Diterlizzi’s Kenny and the Dragon - Endah Saputri (Lexicon, 2015)
This present study aims to examine whether or not DiTerlizzi’s novel entitled Kenny and the Dragon can be categorized as a children’s literature. The story speaks about an adventurous experience of a young rabbit called Kenny to discover the truth about his monstrous-looking friend, Grahame.This study applies formalism approach since it is the most suitable approach to study the intrinsic elements of the novel, which are the plot, character and characterization, and point of view. To support the analysis, library research was conducted alongside the novel itself and supporting articles from reliable websites.The result of the analysis shows that DiTerlizzi’s Kenny and the Dragon meets the requirements for children’s literature since the characteristics of children’s literature suggested by Nodelman are found in the novel.